Search and analysis of genes involved in antibiotic resistance in Chilean strains of Piscirickettsia salmonis. Issue 8 (16th December 2016) - Cartes, C; Isla, A; Lagos, F; Castro, D; Muñoz, M; Yañez, A; Haussmann, D; Figueroa, J
Abstract: Piscirickettsia salmonis is the pathogen causing Piscirickettsiosis. For treatment, the industry mainly uses oxytetracycline and florfenicol, so it is essential to understand the degree of susceptibility of this pathogen to these drugs. But this is still unknown for a large number of P. salmonis strains, as are the molecular mechanisms responsible for greater or lesser susceptibility. However, genes that confer resistance to these antimicrobials have been reported and characterized for this and other bacterial species, among which are membrane proteins that take out the drug. Our results identified differences in the degree of susceptibility to both antibiotics among different Chilean isolated of these bacteria. We analysed 10 available genomes in our laboratory and identified 140 genes likely to be involved in antibiotic resistance. We analysed six specific genes, which suggests that some of them would eventually be relevant in conferring resistance to both antibiotics, as they encode for specific transporter proteins, which increase the number of transcripts when grown in media with these antibiotics. Our results were corroborated with EtBr permeability analysis, which revealed that the LF‐89 strain accumulates this compound and has a reduced capacity to expulse it compared with the field strains.